An insight into the yielding and normal compression of sand with irregularly-shaped particles using DEM - de Bono, John P.; McDowell, Glenn R. (Elsevier, 2015)
The micro mechanics of one-dimensional and isotropic normal compression of granular soil have recently been revealed using the discrete element method. By modelling soil grains as spheres and implementing a new crushing model, the authors have previously investigated the influence of fracture mechanism, particle strengths (and distributions), and the size-hardening law on both the normal compression line and resultant particle size distribution; this resulted in a new compression law. In this work, irregular particle shape is introduced, using ‘clumps’ (groups of spherical particles), allowing different relative densities of the same material to be subjected to normal compression. An investigation into the mechanics of yielding is presented, in which the onset of crushing is related to the average particle octahedral shear stress and ‘yield’ is seen to be a function of the available void space. Beyond yield, the normal compression lines for the clumps at different initial densities are examined and compared to that for spheres. The effect of coordination number and particle shape on the normal compression are studied, and in particular the micro mechanics behind the evolution of a fractal particle size distribution are revealed.